ANALISIS ASPEK GEOMORFOLOGI DESA MEKARJAYA, KECAMATAN CIEMAS, KABUPATEN SUKABUMI, JAWA BARAT - Aliyuddin Jamil; Nana Sulaksana; Pradnya Paramarta Raditya Rendra (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2022)
The shape of the earth's surface that exists today is the result of geological processes that have taken place during the geological period which can show how the characteristics and distribution of the rocks. This research was conducted to find out how the geomorphological conditions were by analyzing the morphographic, morphometric, and morphogenetic aspects as a geomorphological shaper in an area. The research location is in Mekarjaya Village, Ciemas District, Sukabumi Regency, West Java which has geomorphological conditions that are influenced by the existence of old submarine volcano activity which then uplifted and exposed by intensive tectonic processes. The method used in this study combines qualitative and quantitative aspects supported by satellite imagery, data processing applications, and references from previous research. The results of this study show that there are 2 geomorphological units in the study area, namely the Slightly Steep Volcanic Hills Unit and Steep Volcanic Hills Unit with andesitic lava rock distribution and volcanic breccia. The river flow pattern that developed is a rectangular drainage pattern.